ANTIBACTERIAL AND ANTIBIOFILM ACTIVITY OF CU/CU2O NPS AGAINST MULTIDRUG-RESISTANT BACTERIA - Duzhyi, Igor; Myronov, Petro; Ivakhniuk, Tetiana; Pshenychnyi, Roman; Bidakov, Oleksandr; Holubnycha, Viktoriia (Eastern Ukrainian Medical Journal, 2024)
Introduction. Multidrug-resistant (MDR) bacteria are very dangerous and represent a major problem in all areas of healthcare: they often cause diseases that cannot be treated with antibiotics, which leads to long-term ineffective treatment, complications, and high treatment costs. Searching for new antimicrobials is one of the key components of a successful fight against infections caused by MDR. This study was designed to elucidate the antimicrobial and antibiofilm activities of copper/copper oxide nanoparticles (Cu/Cu2O NPs) against MDR bacteria. Methods. Cubic Cu/Cu2O NPs were synthesized by the polyol method. The physicochemical characteristics of the nanoparticles were investigated using transmission electron microscope, X-ray diffraction investigation, energy dispersive spectroscopy and Fourier-transform infrared spectroscopy. Laboratory reference bacterial strains (S. aureus ATCC 25923. E. coli ATCC 25922, P. aeruginosa ATCC 27853) and MDR clinical strains isolated from patients with a purulent process (S. aureus, E. coli, P. aeruginosa) were used to examine the antibacterial effect of nanoparticles. Results. Cubic Cu/Cu2O NPs showed antimicrobial activity against both Gram-negative and Gram-positive bacteria, but the antibiofilm activity of Cu/Cu2O NPs was more promising for targeting Gram-negative bacteria. Cu/Cu2O NPs were less effective against MDR strains of planktonic bacteria in comparison to laboratory reference strains. No significant differences were found between the action of the Cu/Cu2O NPs on biofilms formed with reference laboratory strains or MDR clinical strains. Discussion. The findings of this research may be useful to develop new drugs and approaches for treating infection caused by MDR microorganisms. Further research is warranted to elucidate the underlying mechanisms of Cu/Cu2O NPs action, optimize their formulation, and evaluate their safety and efficacy in preclinical and clinical settings